Transformation and transcendence – reforming news production in the convergent media era - Zhi Li; Yinchang Chen (Trans/Form/Ação)
The present-day networked media ecosystem is distinctly characterized by convergence. Recently, media convergence has experienced rapidly progress both in theoretical circles and in practical applications, and convergence development has inevitably become a leading trend in media development. Media convergence has uniquely transformed the ecology of news, communication and public opinion, in which an overhaul of news production stands out as its main expression. As a result of media convergence, news production has shifted from a traditional linear to a nonlinear mode. Due to the use of video, audio and H5 forms of news in new media, in addition to traditional media primarily based on text and image content, news reporting is now more diverse, visually appealing and innovative. The process of producing news has changed as a result of media convergence, becoming more effective, adaptable and diverse. By studying the impact of media integration on news production, this article aimed to understand how media should be adjusted in the era of integration, how news production should develop and break through, and the general laws of news production in the process of integration development. At the same time, in this context, the research under consideration investigates the impact of media convergence on news production, outlines the way that media can adapt to dynamic landscapes, proposes new methods of news production to promote the progress of the convergence era, and aims to establish the basic principles of news production in integrated development. Under the trend of digitization, networking and informatization, the mode of news production has undergone changes. With the rise of new media and the gradual transformation of traditional media, the news production environment and mode have also undergone profound changes. This article revealed the underlying mechanisms and future trends of this change, which can improve the efficiency and quality of news production and enhance its competitiveness in a diversified media environment. It has important reference value for news organizations, media practitioners and relevant policy makers, and can provide scientific basis for their decision-making.